2011
DOI: 10.1021/ef2001162
|View full text |Cite
|
Sign up to set email alerts
|

NMR Characterization of Pyrolysis Oils from Kraft Lignin

Abstract: The pyrolysis of softwood (SW) kraft lignin was examined at 400, 500, 600, and 700 °C. The yields of pyrolysis oil, char, and gas were determined to be 35−44%, 57−38% and 8−18%, respectively. The pyrolysis oil has a comparable heating value with ethanol and coal. The elevated temperature of 700 °C was found as the point of primary decomposition of lignin and the secondary decomposition of pyrolysis oil. Gel permeation chromatography (GPC) and quantitative 13C and 31P NMR were used to characterize the pyrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
284
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(303 citation statements)
references
References 55 publications
15
284
0
Order By: Relevance
“…The yields of acids and alcohols decreased as the pyrolysis temperature increased. Ben et al also found that the concentration of acetic acid and methanol in light oil produced by lignin pyrolysis decreased as temperature rose [26]. The 13.3% yield of phenols indicated that only a fraction of the EHL decomposition pathway occurred at 350 °C.…”
Section: The Effects Of Pyrolysis Temperature and Timementioning
confidence: 96%
“…The yields of acids and alcohols decreased as the pyrolysis temperature increased. Ben et al also found that the concentration of acetic acid and methanol in light oil produced by lignin pyrolysis decreased as temperature rose [26]. The 13.3% yield of phenols indicated that only a fraction of the EHL decomposition pathway occurred at 350 °C.…”
Section: The Effects Of Pyrolysis Temperature and Timementioning
confidence: 96%
“…The liquid products from pyrolysis are known as pyrolysis oils which separate into two immiscible phases: heavy oil and light oil [79]. A pyrolysis light oil fraction of switch grass used as the sole carbon source in a fermentation with R. opacus resulted in increased oleaginicity (22-26%) and improved lipid titers (0.06-0.12 mg/ml) (Table 1, #6).…”
Section: Lignocellulosic Biomass Pretreatment Strategiesmentioning
confidence: 99%
“…A pyrolysis light oil fraction of switch grass used as the sole carbon source in a fermentation with R. opacus resulted in increased oleaginicity (22-26%) and improved lipid titers (0.06-0.12 mg/ml) (Table 1, #6). The pyrolysis resulted in low molecular weight water-soluble substances in light oil fraction which seems to play a role in oleaginicity and improved lipid titers [79].…”
Section: Lignocellulosic Biomass Pretreatment Strategiesmentioning
confidence: 99%
“…Nevertheless, research into biomass pyrolysis is multi-disciplinary and multi-dimensional. The diverse array of these research activities include advanced analytical chemistry methods for bio-oil characterization [16][17][18], developing kinetic models for the pyrolysis reactions [19], computational fluid dynamic studies [20], design of new reactors [21], developing new heating methods such as microwave assisted pyrolysis [22][23], optimizing the bio-oil yield [24], developing various bio-oil upgrading methods [25], process intensification [26], techno-economic analysis [27,28] and environmental assessment [29], in addition to enterprise-wide and supply chain optimization [30][31][32]. A recent review of the research into biomass fast pyrolysis is provided by Meier et al, [33].…”
Section: Introductionmentioning
confidence: 99%